Análisis del comportamiento del consumidor en las cafeterías y la implementación de un plan de Marketing para su posicionamiento - Jumbo Carreño, Andrea Patricfia (2015)
This research work is carried out in the canton Huaquillas, the reason is to learn which are the tastes, preferences, actual needs, requirements, and demand for its inhabitants, through research, data collection and analysis to check the degree of acceptance of the current and potential consumers, in which it used the theories of reference such as concept, behavior and consumer satisfaction, perspective about how they perceive the cafeteria. The methodology that was used was the model of survey that was conducted to the citizens of the city already mentioned. Within the results of the research carried out we were able to determine that a high percentage of citizens who wish to make this type of service can be found in the canton, because in this there is no, or only to a limited extent, in restaurants, ice cream parlors, soda fountains commonly known as "juguerias". It also details the procedure that was performed to demonstrate the likelihood of developing this project in the future. The purpose of the study is to propose a marketing plan for the introduction and positioning of an innovative service using the various market strategies, and internal policies that enable them to meet the current and new consumer, in the same way was carried out calculations of cost-effectiveness, consumer and offer valuable references that are to be projected goals and targets to medium or long-term. In consequence it has been determined that the implementation of this project would be very feasible, since there is no competition, who decides run would become the pioneer in the canton, and in the province, by being innovative and unique in this market sector as it is offered in this marketing plan, it is estimated that you will get success in the local market.